Perbandingan Pemberian Tablet Fe + Vitamin A dan Tablet Fe + Asam Folat Terhadap Peningkatan Kadar Hemoglobin - Suchi Avnalurini Sharief; Azrida M (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
WHO states that anemia is the 10 biggest health problems in this modern century. Based on Riskesdas (2013), it was reported that the incidence of anemia nationally was 21.7%, of which 18.4% occurred in men and 23.9% in women. Based on age group, anemia sufferers aged 5-14 years were 26.4% and 18.4% in the age group 15-24 years. Of all the age groups, women have the highest risk for anemia, especially teenage girls. The purpose of this study was to determine the comparison of the administration of Fe + Vit A tablets and Fe + Folic acid tablets to elevated Hb levels in DIII midwifery students from the Indonesian Muslim University. This type of research was a Quasi Experimental study with the Post Test Only design approach to Knowing Comparison of Giving Tablets of Fe & Vit A with Fe Tablets & Folic Acid to Increasing Hb Levels in DIII Midwifery Study Program Students at Muslim University of Indonesia. The sample was taken by purposive sampling technique with a total of 32 female students. The results of this study there was a difference in the increase in hemoglobin levels in the group supplementing Fe + Vit A and Fe + Folic Acid tablets. The results of statistical tests using the T-test using Independent Samples Test obtained mean difference value of 0.918, P = 0.039 smaller than the specified significance value of α (0.05), meaning that there was a significant difference between the pretest levels and each good giving. in the group Fe + Vitamin A and Fe + Folic Acid. Keywords: young women; Hb; Fe; vit A; folic acid ABSTRAK WHO menyebutkan bahwa anemia merupakan 10 masalah kesehatan terbesar di abad modern ini. Berdasarkan Riskesdas (2013), dilaporkan bahwa angka kejadian anemia secara nasional adalah sebesar 21,7%, dimana 18,4% terjadi pada laki-laki dan 23,9% terjadi pada perempuan. Berdasarkan kelompok umur, penderita anemia berumur 5-14 tahun sebesar 26,4% dan sebesar 18,4% pada kelompok umur 15-24 tahun. Dari semua kelompok umur tersebut, wanita mempunyai resiko paling tinggi untuk menderita anemia terutama remaja putrid.Tujuan penelitian ini untuk Mengetahui Perbandingan Pemberian Tablet Fe + Vit A dan Tablet Fe + Asam Folat terhadap Peningkatan kadar Hb pada Mahasiswi Prodi DIII Kebidanan Universitas Muslim Indonesia. Jenis penelitian ini adalah penelitian Quasi Experimental dengan pendekatan Post Test Only design untuk Mengetahui Perbandingan Pemberian Tablet Fe & Vit A dengan Tablet Fe & Asam Folat terhadap Peningkatan kadar Hb pada Mahasiswi Prodi DIII Kebidanan Universitas Muslim Indonesia.Adapun Sampel diambil dengan teknik Purposive sampling dengan jumlah 32 mahasiswi.Hasil penelitian ini ada Perbedaan peningkatan kadar Hemoglobin pada kelompok pemberian suplementasi Fe + Vit A dan Tablet Fe + Asam Folat. Hasil uji statistik menggunakan T- test dengan mengunakan Independent Samples Test diperoleh nilai mean difference 0,918, P = 0,039 lebih kecil dari dari nilai kemaknaan yang ditetapkan yakni α (0,05) artinya ada perbedaan yang bermakna antara kadar pretest dengan masing-masing pemberian baik pada kelompok Fe + Vitamin A dan Fe + Asam folat. Kata kunci: remaja putri; Hb; Fe; vit A; asam folat